Preparation method of nano lignocellulose flexible conductive composite gel

By using metal salt-based eutectic solvents to perform nano-lignocellulose conductive composite gels in conductive gels, nano-lignocellulose conductive composite gels with high mechanical properties and high electrical conductivity are prepared, solving the problem of unbalanced performance of traditional conductive gels.

CN119505097AActive Publication Date: 2025-02-25NANJING FORESTRY UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411824945.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-25
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

There is a problem of imbalance between mechanical properties and electrical properties of traditional conductive gels, and the conductivity is difficult to improve.

Method used

The biomass raw materials are nano-treated with polyol/choline chloride/metal salt-based eutectic solvents, and nanolignocellulose with high aspect ratios are prepared, and conductive networks are formed in the gel through nanolignin-metal ion redox reaction.

Benefits of technology

The nano-lignocellulose conductive composite gel with high mechanical properties and high conductivity is achieved, which simplifies the preparation process and overcomes the performance imbalance of traditional conductive gels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505097A_ABST
    Figure CN119505097A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of nano lignocellulose flexible conductive composite gel. The extraction method comprises the following steps: (1) carrying out cooking treatment on a biomass raw material by using a metal salt-based eutectic solvent, and then carrying out mechanical treatment to prepare a nano lignocellulose eutectic solvent dispersion liquid containing nano lignin; (2) adjusting the pH value of the nano lignocellulose eutectic solvent dispersion liquid containing the nano lignin to 8.5; and (3) adding a polymerizable polymerization monomer and an initiator into the dispersion liquid, and rapidly initiating a high polymer at room temperature through a nano lignin-metal ion oxidation-reduction reaction to obtain the nano lignocellulose flexible conductive composite gel. The method comprises the following steps: by taking lignocellulose as a raw material, carrying out efficient nanocrystallization treatment on the biomass raw material through a metal salt-based eutectic solvent of polyol / choline chloride / metal salt to obtain a nano lignocellulose eutectic solvent dispersion liquid with a high length-diameter ratio; the nano lignocellulose flexible conductive composite gel is prepared in one pot through an oxidation-reduction reaction between in-situ generated or exogenously added nano lignin and metal ions, and can be used in the fields of flexible sensing, supercapacitors, stretchable devices and the like. According to the method, complex solvent replacement is not needed, conditions are mild and efficient, and the prepared gel has excellent mechanical properties and high ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-lignocellulose conductive gel materials, and in particular to a method for preparing a nano-lignocellulose flexible conductive composite gel by nano-crystallization of biomass raw materials and in-situ redox reaction thereof in a metal salt-based low eutectic solvent system. Background Art

[0002] Conductive gels have attracted widespread attention in the fields of flexible sensors, batteries, and supercapacitors due to their mechanical flexibility and environmental stability. However, in practical applications, they have problems such as poor mechanical properties and difficulty in improving electrical conductivity.

[0003] Nanocellulose has the advantages of large specific surface area, high degree of chemical modification, good biocompatibility and high mechanical strength. Nanocellulose with high aspect ratio can act as a reinforcing phase in the gel polymer skeleton to improve the mechanical properties of the gel. Nanocellulose can be prepared by a low eutectic solvent (DES), and nanocellulose conductive gel can be prepared by introducing a conductive polymer or monomer. However, the DES used for cellulose nanodispersion is usually a carboxylic acid-based solvent system (such as lactic acid / choline chloride, oxalic acid / choline chloride, citric acid / choline chloride, etc.), which has a low conductivity and cannot meet the requirements of conductive gel for electrochemical performance. Therefore, this technology uses a metal salt-based low eutectic solvent of polyol / choline chloride / metal salt to achieve efficient nano-nanoization of biomass raw materials and the preparation of nano-lignocellulose conductive composite gel with high conductivity.

[0004] Since nanocellulose has poor dispersibility in a high-salt environment, the concentration of metal salts is very important in the construction of metal salt-based deep eutectic solvents of polyols / choline chloride / metal salts. It is necessary to ensure that the size of the hydrated ions of the metal salt can penetrate into the biomass raw material, improve the dispersion and diffusion capacity of the entire deep eutectic solvent to the biomass raw material, and ensure that it maintains a certain metal ion migration ability during the later gel preparation process, thereby improving the conductive properties of the composite gel. In addition, lignin has high redox characteristics, rich methoxyl groups, phenolic hydroxyl groups and other active functional groups, CN118256006A proposes to utilize lignin and metal ions under alkaline conditions The redox reaction is prepared by free radical initiated polymerization to prepare lignin conductive gel, but there are problems such as lignin structure heterogeneity, poor solvent dispersibility, and insufficient catalytic activity. Compared with disordered fragmented lignin, nano lignin has the advantages of uniform size, strong surface charge, and regular morphology, which is conducive to improving its reactivity and greatly improving the mechanical stability of the gel as a reinforcing agent and toughening agent in the gel network. In addition, the hemicellulose in the solvent is rich in hydroxyl, carbonyl and aldehyde groups, which can serve as a stabilizer for nano-lignin, significantly improving the dispersibility of nano-lignin in the gel network and ensuring its high reactivity with metal ions to enhance the conductive properties of the gel.

[0005] In summary, the use of metal salt-based low eutectic solvents of polyols / choline chloride / metal salts to treat biomass raw materials while achieving nano-sizing of cellulose and lignin in biomass not only overcomes the problem of poor dispersibility caused by high salt content, but also the hemicellulose in biomass can wrap nano-lignin to improve the dispersibility of nano-lignin in the gel network, enhance its redox activity, achieve efficient in-situ polymerization of gel, and strengthen and toughen composite conductive gel. The preparation of nano-lignocellulose conductive composite gel under metal-based low eutectic solvents can simplify the process, make full use of the advantages of nano-lignocellulose, and overcome the problem of imbalance between mechanical properties and electrical properties of traditional conductive gels. In view of this, the present invention is proposed. Summary of the invention

[0006] Purpose of the invention: The traditional conductive gel preparation process has problems such as complex reaction process, poor biocompatibility, and imbalance between mechanical properties and electrical properties under stress-strain transmission. In this paper, lignocellulose is used as raw material, and the biomass raw material is efficiently nano-processed by a metal salt-based low eutectic solvent of polyol / choline chloride / metal salt to obtain a high aspect ratio nano-lignocellulose low eutectic solvent dispersion; then, the nano-lignocellulose flexible conductive composite gel is prepared in one pot through the redox reaction between the in-situ generated or exogenously added nano-lignin and metal ions. The hemicellulose encapsulation of lignin is efficiently regulated to prepare nano-lignin, ensuring efficient catalytic activity and gel enhancement effect. The entire system gives full play to the advantages of each component to prepare a nano-lignocellulose conductive composite gel with high mechanical properties and high conductivity. In addition, the present invention has the characteristics of mild reaction conditions, simple and efficient preparation process, high component utilization rate, and excellent product performance.

[0007] Technical solution: In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0008] 1. A method for preparing a nano-lignocellulose flexible conductive composite gel, characterized in that it comprises the following steps:

[0009] S1. Cooking a biomass raw material with a metal salt-based low eutectic solvent, and then preparing a nano-lignin-containing nano-lignocellulose low eutectic solvent dispersion by mechanical treatment; the biomass raw material is any one of hemp, wood, grass, and bamboo, or a combination of two or more thereof;

[0010] S2, adjusting the pH of the nano-lignocellulose low eutectic solvent to 8.5, adding polymerizable monomers and initiators to the dispersion prepared in step S1, and rapidly initiating polymers at room temperature through the nano-lignin-metal ion redox reaction to obtain a nano-lignocellulose flexible conductive composite gel.

[0011] 2. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 is characterized in that additional nano-cellulose or additional nano-lignin is added to the nano-lignocellulose low eutectic solvent dispersion containing nano-lignin in step S1; the additional nano-cellulose is any one of hemp nano-cellulose, wood nano-cellulose, grass nano-cellulose, and bamboo nano-cellulose; the additional nano-lignin is any one of homologous lignin, alkali lignin, low eutectic solvent lignin, and lignin sulfonate in the biomass raw material.

[0012] 3. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 or 2, characterized in that the metal salt-based low eutectic solvent in step S1 is polyol / choline chloride / metal salt, the polyol is any one or a combination of two or more of glycerol, ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, and neopentyl glycol, and the metal salt is any one of aluminum chloride, ferric chloride, zinc chloride, cupric chloride, magnesium chloride, lithium chloride, and potassium chloride. The molar ratio of polyol / choline chloride / metal salt is 2:1:0.2, and the solid-liquid ratio of biomass raw material to low eutectic solvent is 1:6-1:10.

[0013] 4. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 or 2, characterized in that the cooking conditions in step S1 are 80-140°C and the insulation time is 1-5 hours.

[0014] 5. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 or 2, characterized in that the diameter of the nano-lignocellulose in the nano-lignocellulose low eutectic solvent dispersion in step S1 is 20-100 nm, the content is 0.1-10%, and the particle size of the nano-lignin is 50-200 nm, and the content is 0.1-5%.

[0015] 6. A method for preparing a flexible conductive composite gel of nano-lignocellulose, characterized in that the polymerizable monomer in step S2 is any one of acrylamide, acrylic acid, and glycidyl methacrylate, or a combination of two or more thereof; the initiator in step S2 is any one of ammonium persulfate, 2,2'-azo(2-methylpropylamidine) dihydrochloride, potassium persulfate, and benzoyl peroxide, or a combination of two or more thereof; the mass of the polymerizable monomer accounts for 20wt% of the nano-lignocellulose low eutectic solvent with a pH of 8.5, and the amount of the initiator accounts for 0.5wt% of the polymerizable monomer.

[0016] 7. A nano-lignocellulose flexible conductive composite gel, characterized in that it is prepared by the method for preparing a nano-lignocellulose flexible conductive composite gel according to any one of claims 1 to 6. The nano-lignocellulose flexible conductive composite gel has a relatively high conductivity of 5-26.1 mS / cm.

[0017] 8. The nano-lignocellulose flexible conductive composite gel according to claim 7, characterized in that the nano-lignocellulose flexible conductive composite gel has excellent mechanical properties, a tensile stress of 60-485 kPa, and a tensile strain of 300-1400%.

[0018] 9. Application of nano-lignocellulose flexible conductive composite gel, characterized in that the nano-lignocellulose flexible conductive composite gel as described in claims 7-8 is used in the fields of supercapacitors, batteries, flexible sensors, soft robots, and stretchable components.

[0019] Beneficial effects: Compared with the prior art, the advantages of the present invention include:

[0020] 1) The present invention uses a metal salt-based low eutectic solvent to nano-size lignocellulose, and gently and efficiently prepares nano-lignocellulose with a high aspect ratio and good dispersion performance, thereby avoiding the cutting effect of traditional carboxylic acid-based low eutectic solvents on fibers.

[0021] 2) A metal salt-based low eutectic solvent containing nano-lignocellulose is used as a gel precursor to avoid a complex solvent replacement process, thereby preparing a high-strength, high-ionic-conductivity, flexible conductive composite gel while ensuring the utilization of all components of the system.

[0022] 3) Metal salt-based low eutectic solvents can not only efficiently prepare nano-lignocellulose, but also construct nano-lignin-metal ion redox reactions, and prepare flexible conductive composite gels without the need for additional energy introduction, thus achieving green and efficient construction of materials.

[0023] 4) The nano-lignocellulose flexible conductive composite gel prepared by the present invention has excellent toughness and conductivity, and can be used for the electrolyte part of supercapacitors, and can also be used for the conduction of flexible electronic devices, and real-time detection of small movements of the human body, such as joint movements, etc. It provides a broad application prospect for the high-value utilization of cellulose in a low eutectic solvent system. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the preparation process of nano-lignocellulose flexible conductive composite gel;

[0025] Figure 2 is a scanning electron microscope photo of the prepared nano-lignocellulose and its particle size distribution;

[0026] Figure 3 It is based on the scanning electron microscope photo and particle size distribution of controllably prepared nano-lignin in lignin nanocellulose DES dispersion;

[0027] Figure 4It is the X-ray photoelectron spectrum and infrared spectrum obtained by the preparation of nano-lignin-metal redox process;

[0028] Figure 5 This is a real photo of the prepared nano-lignocellulose flexible conductive composite gel;

[0029] Figure 6 is the stress-strain curve of the prepared nano-lignocellulose flexible conductive composite gel;

[0030] Figure 7 The conductivity of the prepared nano-lignocellulose flexible conductive composite gel;

[0031] Figure 8 The prepared nano-lignocellulose flexible conductive composite gel is applied in flexible sensing;

[0032] Fig. 9 The invention relates to the application of the prepared nano-lignocellulose flexible conductive composite gel in supercapacitor gel electrolyte. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings, technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the examples of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The nano-lignocellulose used in the present invention can be prepared by mechanical dispersion such as colloid mill, ultrasonic crushing, disc mill, PFI refiner, ultrafine grinding, high-pressure homogenization, etc. In the following examples, the nano-lignocellulose prepared by mechanical dispersion of colloid mill is used to illustrate the present invention.

[0035] Example 1

[0036] Take 5g of hemp lignocellulose raw material, mix it evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-lignocellulose. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-lignocellulose flexible conductive composite gel at room temperature. The nano-lignocellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 100kPa and 738%, respectively, and its conductivity is 7.4mS / cm.

[0037] Example 2

[0038] Take 5g of hemp lignocellulose raw material, mix it evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath digester at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-lignocellulose. Add 1wt% of homologous nano-lignin, adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-lignocellulose flexible conductive composite gel at room temperature. The nano-lignocellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 455kPa and 800%, respectively, and its conductivity is 18.7mS / cm. The influence of different amounts of nano-lignin added on the gel performance was investigated, and the results are shown in the following table: Homologous lignin has good dispersibility in metal salt-based low eutectic solvents, and the uniform filling of lignin inside the gel plays a reinforcing role. As the lignin content increases, a large amount of lignin filled inside the gel is not conducive to uniform network construction, and the decrease in internal uniformity leads to a decrease in performance.

[0039] Additional added nano-lignin content (wt%) Stress / strain (kPa / %) Conductivity (mS / cm) 0.1 60 / 1400 5 1 455 / 800 18.7 5 308 / 505 15.5

[0040] Example 3

[0041] Take 5g of hemp lignocellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath digester at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-lignocellulose. Then add 1wt% homologous nano-lignin (average particle size of 50nm). Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano-lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano-lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress-strain is 455kPa and 800%, respectively, and the conductivity is 18.7mS / cm. The influence of different average particle sizes of nano-lignin on gel performance was explored, and the results are as follows: The larger the average particle size of nano-lignin, the worse the dispersibility in the gel, and the uneven gel network leads to performance degradation.

[0042] Average particle size of additional nano-lignin (nm) Stress / strain (kPa / %) Conductivity (mS / cm) 50 455 / 800 18.7 100 415 / 755 15.2 200 360 / 620 13.5

[0043] Example 4

[0044] Take 5g of hemp lignocellulose raw material, mix it evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath digester at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing wood nanocellulose. Then add 1wt% alkali lignin (average particle size of 50nm). Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano-lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano-lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress-strain is 350kPa and 1000%, respectively, and the conductivity is 16.2mS / cm. The effects of different types of lignin on gel properties were explored, and the results are as follows: homologous lignin is obtained by pretreatment with metal-based low eutectic solvents, alkali lignin is obtained by alkali pulping, and lignin sulfonate is obtained by sulfite pulping. Homologous lignin can regenerate the stripped lignin macromolecules into nano-lignin due to the presence of polyols. Nano-lignin with high compatibility and good dispersibility can significantly improve the gel performance. Alkali lignin and lignin sulfonate require solvent regeneration, have uneven size and poor dispersibility, and have limited improvement on gel performance.

[0045] Additional nano-lignin types Stress / strain (kPa / %) Conductivity (mS / cm) Homologous lignin 455 / 800 18.7 Alkali lignin 350 / 630 16.2 Lignin sulfonate 380 / 705 15.8

[0046] Example 5

[0047] Take 5g of hemp lignocellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath digester at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano lignocellulose. Add 2wt% of nanocellulose with a diameter of 20nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress-strain is 452kPa and 1000%, respectively, and the conductivity is 19.3mS / cm. The effect of adding different amounts of nanocellulose on the gel properties was explored, and the results are as follows: Nano lignin can be used as a rigid filler to enrich the internal network of the gel, and uniformly distributed nano lignin plays a positive role in the gel performance, but excessive nano lignin will destroy the uniformity of the gel network and reduce the gel performance.

[0048] Additional nanocellulose content (wt%) Stress / strain (kPa / %) Conductivity (mS / cm) 1 335 / 1050 16.2 2 452 / 1000 19.3 10 300 / 625 8.5

[0049] Example 6

[0050] Take 5g of hemp lignocellulose raw material, mix it evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath digester at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing wood nanocellulose. Add 1wt% of homologous lignin (average particle size of 50nm) and 2wt% of nanocellulose with an average diameter of 50nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-lignocellulose flexible conductive composite gel at room temperature. The nano-lignocellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 380kPa and 850%, respectively, and its conductivity is 17.3mS / cm. The effect of adding nanocellulose with different diameters on the gel performance was also investigated. The results are shown in the following table: the larger the diameter of the nanocellulose, the smaller the aspect ratio, the more evenly the nanocellulose with a high aspect ratio is distributed in the gel network, and the more obvious the improvement in gel performance is.

[0051] Diameter of additional nanocellulose (nm) Stress / strain (kPa / %) Conductivity (mS / cm) 20 452 / 1000 19.3 50 380 / 850 17.3 100 300 / 780 15.5

[0052] Example 7

[0053] Take 5g of hemp lignocellulose raw material, mix it evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing wood nanocellulose. Add 1wt% homologous lignin (average particle size of 50nm) and 2wt% nanocellulose with a scale of 20nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-lignocellulose flexible conductive composite gel at room temperature. The nano-lignocellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 485kPa and 1300%, respectively, and its conductivity is 26.1mS / cm.

[0054] Example 8

[0055] Take 5g of poplar wood cellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-cellulose. Add 1wt% homologous lignin (average particle size of 50nm) and 2wt% nanocellulose with a scale of 20nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-cellulose flexible conductive composite gel at room temperature. The nano-cellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 168kPa and 665%, respectively, and its conductivity is 18.2mS / cm. The effects of different biomass raw materials on gel performance were also investigated, and the results are as follows: hemp raw materials are light in weight, and their fibers are thin and long, so they can be used as excellent nanofillers to enhance the performance of gels; poplar and bamboo raw materials are hard, have short fibers, have limited pretreatment effects, and have low fiber aspect ratios, which have limited effects on enhancing gel performance.

[0056] Biomass raw materials Stress / strain (kPa / %) Conductivity (mS / cm) Hemp 485 / 1300 26.1 Poplar 168 / 665 18.2 Bamboo 125 / 675 18.6

[0057] Example 9

[0058] Take 5g of hemp lignocellulose raw material, mix it evenly with propylene glycol / zinc chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-lignocellulose. Add 1wt% homologous lignin (average particle size of 50nm) and 2wt% nanocellulose with a scale of 20nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-lignocellulose flexible conductive composite gel at room temperature. The nano-lignocellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 320kPa and 850%, respectively, and its conductivity is 23.2mS / cm. The effects of different types of low eutectic solvents on gel properties were investigated, and the results are shown in the following table: Choline chloride, as a common hydrogen bond acceptor for low eutectic solvents, can significantly reduce the viscosity of low eutectic solvents and improve liquid stability. Low viscosity low eutectic solvents have stronger penetration effects and high pretreatment efficiency. Uniform low eutectic solvent dispersions are beneficial to improving gel properties. When zinc chloride and lithium chloride are used as hydrogen bond acceptors, the solution viscosity is larger and more time-consuming, which is not conducive to improving gel properties.

[0059] Types of deep eutectic solvents Stress / strain (kPa / %) Conductivity (mS / cm) Glycerol / Choline Chloride / Aluminum Chloride 485 / 1300 26.1 Glycerol / Zinc Chloride / Aluminum Chloride 320 / 850 23.2 Glycerol / Lithium Chloride / Aluminum Chloride 450 / 1200 21.3

[0060] Example 10

[0061] Take 5g of hemp lignocellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 140℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-lignocellulose. Add 1wt% homologous lignin (average particle size of 50nm) and 2wt% nanocellulose with a scale of 20nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to prepare a nano-lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano-lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress-strain is 320kPa and 800%, respectively, and the conductivity is 16.7mS / cm. The effect of cooking temperature on gel properties was also investigated, and the results are shown in the following table: Increasing the cooking temperature can enhance the penetration of the liquid into the biomass raw material, obtaining a highly dispersible and uniform low eutectic solvent dispersion, which effectively improves the gel properties; excessively high cooking temperature exacerbates the degradation of the biomass raw material, and the low eutectic solvent dispersion is difficult to ensure gel properties.

[0062] Cooking temperature (℃) Stress / strain (kPa / %) Conductivity (mS / cm) 80 125 / 675 18.6 100 485 / 1300 26.1 140 320 / 800 16.7

[0063] Embodiment 11

[0064] Take 5g of hemp lignocellulose raw material, mix it evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath digester at 100℃ for 1h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano-lignocellulose. Add 1wt% homologous lignin (average particle size of 50nm) and 2wt% nanocellulose with a scale of 20nm. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano-lignocellulose flexible conductive composite gel at room temperature. The nano-lignocellulose flexible conductive composite gel was subjected to mechanical and electrical measurements to characterize its mechanical properties and conductivity. Its stress-strain is 325kPa and 605%, respectively, and the conductivity is 16.7mS / cm. The effect of different holding times on the gel properties was investigated, and the results are shown in the following table: Prolonging the holding time will make the low eutectic solvent and the biomass raw material mix more evenly, obtaining a low eutectic solvent dispersion with high dispersibility, which effectively improves the gel properties; too long a holding time will degrade the biomass raw material, making it difficult to further improve the gel properties.

[0065] Insulation time (h) Stress / strain (kPa / %) Conductivity (mS / cm) 1 325 / 605 16.7 2 485 / 1300 26.1 5 265 / 820 17.3

[0066] Example 12

[0067] Take 5g of hemp lignocellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:8, and keep it warm in an oil bath digester at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion containing nano lignocellulose. Add 1wt% homologous lignin (average particle size of 50nm), add 2wt% nanocellulose with a scale of 20nm, adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress-strain is 280kPa and 825%, respectively, and the conductivity is 19.2mS / cm. The effect of different solid-liquid ratios on the gel properties was also explored, and the results are as follows: As the solid-liquid ratio decreases, the biomass raw material content decreases, the low wood fiber content is not conducive to the construction of the gel network, and the gel performance decreases.

[0068] Solid-liquid ratio Stress / strain (kPa / %) Conductivity (mS / cm) 1 / 6 485 / 1300 26.1 1 / 8 280 / 825 19.2 1 / 10 100 / 765 16.2

[0069] Comparative Example 1

[0070] Take 5g of hemp lignocellulose raw material, mix it evenly with propylene glycol / choline chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it in an oil bath cooker at 100℃ for 2h. After grinding in a colloid mill for 40min, no low eutectic solvent dispersion containing nano-lignocellulose can be obtained. It can be seen that the use of low eutectic solvents without metal salts cannot successfully prepare wood nanocellulose, and ultimately cannot prepare nano-lignocellulose flexible conductive composite gel.

[0071] Comparative Example 2

[0072] Take 5g of cellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion of nanocellulose. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate. Metal-based low eutectic solvent nanocellulose flexible conductive composite gel cannot be prepared at room temperature. It can be seen that nano-lignocellulose flexible conductive composite gel cannot be successfully prepared at room temperature without nano-lignin.

[0073] Comparative Example 3

[0074] Take 5g of cellulose raw material, mix it evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep it warm in an oil bath cooker at 100℃ for 2h. Grind it in a colloid mill for 40min to obtain a low eutectic solvent dispersion of nanocellulose. Add lignin additionally, adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate. Nano-lignocellulose flexible conductive composite gel cannot be prepared at room temperature. It can be seen that the fragmented lignin particles are uneven and have low nanometer size, resulting in poor polymerization activity, and nano-lignocellulose flexible conductive composite gel cannot be successfully prepared at room temperature.

[0075] Comparative Example 4

[0076] Take 5g of cellulose raw material and 1g of lignin, mix them evenly with propylene glycol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep them warm in an oil bath digester at 100℃ for 2h. Grind in a colloid mill for 40min to obtain a low eutectic solvent dispersion of nano-lignocellulose. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano-lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano-lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress strain is 80kPa and 525%, respectively, and its conductivity is 5mS / cm. It can be seen that the lack of hemicellulose makes it difficult for lignin to form nano-lignin with good uniformity and uniform size under low eutectic solvents. The poor polymerization activity and uneven polymerization during the gel preparation process lead to poor performance of the prepared nano-lignocellulose flexible conductive composite gel.

[0077] Comparative Example 5

[0078] Take 5g of cellulose raw material, 1g of lignin and 1g of xylan, mix them evenly with glycerol / choline chloride / aluminum chloride low eutectic solvent at a solid-liquid ratio of 1:6, and keep them warm in an oil bath cooker at 100℃ for 2h. Grind in a colloid mill for 40min to obtain a low eutectic solvent dispersion of nano-lignocellulose. Adjust the pH to 8.5, add 20wt% acrylamide monomer to the dispersion, and add 0.5wt% ammonium persulfate to make a nano-lignocellulose flexible conductive composite gel at room temperature. Mechanical and electrical measurements were performed on the nano-lignocellulose flexible conductive composite gel to characterize its mechanical properties and conductivity. Its stress-strain is 105kPa and 638%, respectively, and its conductivity is 6.2mS / cm. It can be seen that the addition of exogenous hemicellulose plays a limited role in the formation of nano-lignin, and it is necessary to directly use natural biomass raw materials and low eutectic solvents to prepare gels in one pot.

[0079] Scanning electron microscope photos of the lignocellulose raw material and the nano-lignocellulose prepared in Example 1, and the particle size distribution are shown in FIG. Figure 1 Example 1 Scanning electron microscope images and particle size distribution of nano-lignin prepared in a controlled manner in a lignin nanocellulose DES dispersion are shown in FIG. Figure 2 This indicates that high aspect ratio nano-lignocellulose and uniformly dispersed nano-lignin can be efficiently prepared after metal salt-based deep eutectic solvent cooking and mechanical treatment.

[0080] The X-ray photoelectron spectrum of the redox reaction between the nano-lignin in the nano-lignocellulose and the metal ions in Example 1 is as follows: Figure 3 The introduction of metal leads to an increase in the C=O peak area, indicating that the -OH and -OCH3 groups on the surface of nanolignin are oxidized to quinone / semiquinone. Figure 3 c shows that nano-lignin has a peak at 1265 cm -1 The -OH peak at 40° is weakened, which is due to the effective oxidation of the methoxyl groups of nano-lignin. This indicates that the presence of metal ions successfully oxidizes the phenolic hydroxyl and methoxyl groups in nano-lignin to form quinone / semiquinone structures.

[0081] The nano-lignocellulose flexible conductive composite gel prepared in Example 1 is as follows Figure 4 This indicates that the excellent combination of metal salt-based deep eutectic solvent and wood fiber raw materials gives the flexible conductive composite gel flexible and wide application properties.

[0082] The stress-strain curves of the nano-lignocellulose flexible conductive composite gels prepared in Examples 3, 5, and 7 are as follows: Figure 5 As shown, due to the good interfacial compatibility between the metal salt-based low eutectic solvent and wood nanocellulose, as the content of nanolignin and nanocellulose increased, the stress-strain increased to 483.08 kPa, 1294.67%.

[0083] The conductivity of the nano-lignocellulose flexible conductive composite gel prepared in Examples 3, 5 and 7 is as follows: Figure 6 As shown, due to the high ionic conductivity of the metal salt-based low eutectic solvent, the increased content of nano-lignin and nano-cellulose provides more ion transmission channels, and the conductivity is increased to 26.1mS / cm.

[0084] The nano-lignocellulose flexible conductive composite gel prepared in Example 7 was charged at a constant voltage to detect the ability of the flexible conductive composite gel to recognize subtle movements of the human body. Figure 7 As shown, the nano-lignocellulose flexible conductive composite gel can accurately identify subtle movements of the human body and transmit stable electrical signals. This shows that the present invention has excellent application prospects in the fields of flexible electronic devices, wearable devices, etc.

[0085] The nano-lignocellulose flexible conductive composite gel prepared in Example 7 was assembled into a flexible supercapacitor, such as Figure 8 As shown, the flexible supercapacitor has excellent specific capacitance and remains stable during multiple charge and discharge cycles, which shows that the present invention has broad application prospects in the field of energy storage.

Claims

1. A method for preparing a nano-lignocellulose flexible conductive composite gel, characterized in that: The following steps are involved: S1. Cooking a biomass raw material with a metal salt-based low eutectic solvent, and then preparing a nano-lignin-containing nano-lignocellulose low eutectic solvent dispersion by mechanical treatment; the biomass raw material is any one of hemp, wood, grass, and bamboo, or a combination of two or more thereof; S2, adjusting the pH of the nano-lignocellulose low eutectic solvent to 8.5, adding polymerizable monomers and initiators to the dispersion prepared in step S1, and rapidly initiating polymers at room temperature through the nano-lignin-metal ion redox reaction to obtain a nano-lignocellulose flexible conductive composite gel.

2. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1, characterized in that: Add additional nanocellulose or additional nanolignin to the nano-lignocellulose low eutectic solvent dispersion containing nanolignin in step S1; the additional nanocellulose is any one of hemp nanocellulose, wood nanocellulose, grass nanocellulose, and bamboo nanocellulose; the additional nanolignin is any one of homologous lignin, alkali lignin, low eutectic solvent lignin, and lignin sulfonate in the biomass raw material.

3. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 or 2, characterized in that: The metal salt-based deep eutectic solvent in step S1 is polyol / choline chloride / metal salt, the polyol is any one or a combination of two or more of glycerol, ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, and neopentyl glycol, and the metal salt is any one of aluminum chloride, ferric chloride, zinc chloride, cupric chloride, magnesium chloride, lithium chloride, and potassium chloride. The molar ratio of polyol / choline chloride / metal salt is 2:1:0.2, and the solid-liquid ratio of the biomass raw material to the deep eutectic solvent is 1:6-1:

10.

4. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 or 2, characterized in that: In step S1, the cooking condition is 80-140° C. and the heat preservation time is 1-5 hours.

5. The method for preparing a nano-lignocellulose flexible conductive composite gel according to claim 1 or 2, characterized in that: In the nano-lignocellulose low eutectic solvent dispersion in step S1, the diameter of the nano-cellulose is 20-100 nm, the content is 1-10%, and the particle size of the nano-lignin is 50-200 nm, the content is 0.1-5%.

6. A method for preparing a nano-lignocellulose flexible conductive composite gel, characterized in that: The polymerizable monomer in step S2 is any one of acrylamide, acrylic acid, and glycidyl methacrylate, or a combination of two or more thereof; the initiator in step S2 is any one of ammonium persulfate, 2,2'-azo(2-methylpropylamidine) dihydrochloride, potassium persulfate, and benzoyl peroxide, or a combination of two or more thereof; the mass of the polymerizable monomer accounts for 20wt% of the pH=8.5 nano-lignocellulose low eutectic solvent, and the amount of the initiator accounts for 0.5wt% of the polymerizable monomer.

7. Nano-lignocellulose flexible conductive composite gel, characterized in that: The nano-lignocellulose flexible conductive composite gel is prepared by the preparation method of any one of claims 1 to 6. The nano-lignocellulose flexible conductive composite gel has a relatively high conductivity of 5-26.1 mS / cm.

8. The nano-lignocellulose flexible conductive composite gel according to claim 7, characterized in that: The nano-lignocellulose flexible conductive composite gel has excellent mechanical properties, a tensile stress of 60-485 kPa, and a tensile strain of 300-1400%.

9. Application of nano-lignocellulose flexible conductive composite gel, characterized in that: The nano-lignocellulose flexible conductive composite gel as described in claims 7-8 is used in the fields of supercapacitors, batteries, flexible sensors, soft robots, and stretchable components.

Citation Information

Patent Citations

  • A method of preparing nanometer lignin by utilizing a eutectic solvent

    CN107200851A

  • Preparation method of lignocellulose nanofibers

    CN110130136A

  • Preparation method of micro-nano lignocellulose composite material, composite material and application

    CN113136038A

  • Flexible conductive composite material with high strength and high nanocellulose content as well as preparation method and application of flexible conductive composite material

    CN115197370A

  • Hydrogel loaded with nano lignin-nano niobium composite material as well as preparation method and application of hydrogel

    CN116284866A